Analisis Kandungan Mineral Pasir Pantai Bajul Mati Kabupaten Malang Menggunakan XRF dan XRD - Sumari Sumari; Yana Fajar Prakasa; Muhammad Roy Asrori; Dinar Rachmadika Baharintasari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Mineral exploration in Indonesia has not been evenly distributed, so a study with title analysis of the sand mineral content of Bajul Mati Malang Regency was carried out using XRF and XRD. The aims of this study to determine the percentage of mineral that containing in the sand of Bajul Mati beach in Malang Regency. The instruments used XRF and XRD where the samples were placed in a sample holder and irradiated with X-rays then. The result of analysis of mineral content and metal oxide in Bajul Mati beach sand showed that the beach sand of Bajul Mati has the big potential to be used as a base for making nanomaterials. The results of analysis of XRF showed that the content of SiO2 was 46.7% and the results of analysis of XRD showed that the SiO2 mineral has the quartz phased. Bajul Mati beach sand has the potential to be a source of mineral material.